Nutritional characterization of carobs and traditional carob products. Issue 8 (4th October 2018) - Papaefstathiou, Eleni; Agapiou, Agapios; Giannopoulos, Stelios; Kokkinofta, Rebecca
Abstract: Twenty traditional carob products were measured for their nutritional composition, and their results were compared with the pulp of Cypriot carob cultivars. Moisture, ash, fat, proteins, sugars, dietary fibers, minerals, caffeine‐theobromine, carbohydrates, and energy value were determined. Fluctuations of the nutritional composition values based on the ingredients' chemical synthesis and product manufacturing process were noted. Only 60% of the products had a label indicating their nutritional value, and the majority of them (75%) were consistent with that of labeling. Chemometric analyses distinguished the carob products according to their type and the discriminator components highlighted their particular nutritional value. Carobs can be characterized as functional foods with low‐fat content, high content in dietary fibers, and high content and/or source of minerals; however, carob products partially satisfied those health and nutritional claims as expected. This pilot research contributes to the nutritional estimation of carob and highlights the traditional carob products. Abstract : Carob pods and their products were analysed for their nutritional composition. Carobs can be characterized as functional foods (fat, dietary fibers and minerals). Their nutritional value was highlighted using Chemometrics